Weaponizing conspiracy theories - Eiríkur Bergmann Einarsson 1969- (Conspiracy theories, 2025)
"This book analyses the discursive weaponization of conspiracy theories. In an era where truth and fiction converge, nativist populist leaders wield conspiracy theories as political weapons. This text examines the interplay between populism and conspiracism, probing their impact on democratic processes and exploring their broader political implications. The work dissects three predominant conspiracy theories: the Eurabia theory in Europe, the Deep State in the United States, and anti-Western narratives in Russia. It shows their evolution from fringe ideas to mainstream political tools and reveals the leaders' triple strategy: constructing external threats, demonizing internal elites, and positioning themselves as protectors of the 'true people.' It also examines how digital media facilitates the spread of these narratives, undermining institutional trust and fuelling extremism. Weaponizing Conspiracy Theories serves as a guide to recognize and navigate the distorted realities reshaping our world. It offers essential insights into the complex dynamics of 21st-century global politics. The author argues that to properly understand the functions of contemporary politics, into which conspiracy theories and populism are now deeply integrated, we must both examine the impact that conspiracy theories have on people's understandings of the world and how populist politicians can appeal to these beliefs. It will be of interest to students and scholars of conspiracy theories, populism and contemporary politics."